Antioxidant and Antimicrobial Activity of Hydroethanolic Leaf Extracts from Six Mediterranean Olive Cultivars - Vida Šimat; Danijela Skroza; Giulia Tabanelli; Martina Čagalj; Federica Pasini; Ana María Gómez-Caravaca; Carmen Fernández-Fernández; Meta Sterniša; Sonja Smole Možina; Yesim Ozogul; Ivana Generalić Mekinić (MDPI AG, 2022)
Phenolic profiles, antioxidant, and antimicrobial activities of hydroethanolic olive leaf extracts from six Mediterranean olive cultivars (Croatian: Lastovka, Levantinka, Oblica; Italian: Moraiolo, Frantoio, Nostrana di Brisighella) were investigated. As expected, various distributions of phenolic levels were observed for each cultivar and the total phenolic content showed high variability (ranging from 4 to 22 mg GAE/g of dry extract), with the highest amount of phenolics found in the Oblica sample, which also provided the highest antiradical (ORAC) and reducing activity (FRAP). The screening of individual compounds was performed by HPLC-PDA-ESI-QTOF-MS and the main detected compounds were oleuropein, hydroxytyrosol, oleoside/secologanoside, verbascoside, rutin, luteolin glucoside, hydroxyoleuropein, and ligstroside. While the antioxidant activity of the samples was relatively high, they showed no bactericidal and bacteriostatic activity against E. coli and S. Typhimurium; weak activity against Staphylococcus aureus, Bacillus cereus, and Listeria innocua; and inhibitory effects against Campylobacter jejuni at 0.5 mg dry extract/mL. The obtained results support the fact that olive leaf extracts, and especially those from the Oblica cultivar, could potentially be applied in various industries as natural preservatives and effective and inexpensive sources of valuable antioxidants.